Evaluation of Peripheral Blood Lymphocytes Proliferation in Botteng Village, Mamuju Inhabitants Using Binucleate Index - Ramadhani, Dwi; Sardini, Sri; Lubis, Masnelli; Syaifudin, Mukh (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2017)
Botteng Village in Mamuju, West Sulawesi was known for the high natural background radiation exposure. Botteng Village inhabitants exposed to high natural radiation in their daily life. Radiation exposure can inhibit the mitosis mechanism at various phases. Our previous study revealed that mitotic and nuclear division indexes in Botteng Village inhabitants were lower compared to control samples. To validate our previous study results here we evaluate the binucleate index in peripheral blood lymphocytes of Botteng Village inhabitants. Blood samples were collected from thirteen healthy adult subjects in Botteng Village and thirteen healthy adult subjects in normal background radiation area. Binucleate index was calculated as the proportion of binucleated cell (BNC) in 500 cells for each sample. Our study showed that the BI in Botteng Village was higher compared to control group (23.58 ± 9.60 vs 23.47 ± 6.24). Statistical analysis revealed that the different was not significant (p=0.973). It is possible that the small sample numbers used in this study were not adequate to represent the BI value in Botteng Village inhabitants. This study also showed that there was insignificant difference of BI in respect to gender and age for all samples. Further study using larger sample number should be conducted to ensure the possibility of BI to evaluate the effect of chronic low radiation dose exposure on lymphocytes proliferation.